2019
DOI: 10.21203/rs.2.12199/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The social media intervention for lower back pain education study (SMILE): a protocol for a randomized trial to reduce occupational low back pain in nursing professionals

Abstract: Background Low back pain in nursing profession remains an important health issue. This study aims to assess whether a theory based interactive social media intervention could change job-related risk behaviors among nursing personnel. Methods This is a community-randomized controlled trial. Three settings of hospitals will randomly be assigned to the study arms: Intervention setting 1 receiving an in-person educational package; intervention setting 2 receiving the same material a web-based; and a control settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…The present study verified that the designed educational intervention were effective on promoting knowledge, attitude and behaviors of clinical workers in intervention group. These results are in line with the results of the previous studies [10,11] . In addition , the existed study [12] , Which was conducted in 2017 regarding the effect of back school workshops on the level of knowledge and attitude of nurses , showed that after training program a significant difference was seen in knowledge and attitude of the participants that is consistent with the results of present study.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The present study verified that the designed educational intervention were effective on promoting knowledge, attitude and behaviors of clinical workers in intervention group. These results are in line with the results of the previous studies [10,11] . In addition , the existed study [12] , Which was conducted in 2017 regarding the effect of back school workshops on the level of knowledge and attitude of nurses , showed that after training program a significant difference was seen in knowledge and attitude of the participants that is consistent with the results of present study.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study the attitude of the intervention group was significantly improved after taking part in intervention program. In this regard, previous studies [11,13] have supported this finding of the present study in terms of significance improvement of attitude of the participants after the intervention. In the study of Kazemi et al [11] , between the two methods of face-to-face and virtual education, the change in attitude in the direct education method in the first trimester was due to the direct relationship between educator and learner and the possibility of more exchange, although the effect of virtual education on longer evaluation, has been obtained because of virtual education benefits such as greater accessibility and lower implementation costs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As part of a trial [18], a community randomized-control trial study was conducted to develop and evaluate intervention based on the PRECEDE-PROCEED Model on promoting behaviors of low back health via two educational approaches including social media and in-person education approaches. The study was adopted from the declaration of Helsinki and received ethical approval from the Human Ethics Committee at the University of Tarbiat Modares, Tehran, Iran (IR.…”
Section: Methodsmentioning
confidence: 99%